Teaching French Literature in a Foreign Language: A Gap Story - Poletti, Marie Laure (Journal of Modern Languages, 2017)
This study considers the methods of teaching French literature applicable in other languages. It also compares the relation between researchers who are striving for the more abstract and power models and those who are interested in the intersubjective part in the historical of personal reading variations only.